PENGARUH NPF, CAR, DAN FDR TERHADAP PROFITABILITAS PADA BANK UMUM SYARIAH DI INDONESIA PERIODE 2016-2020 - Fira Prasilia Dwintama; Satrio Ramadhan; Iman Fauqa Darajat; Nurul Hak; Kustin Hartini (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2021)
ABSTRACTThis study aims to determine the effect of NPF, CAR, FDR on Profitability at Islamic Commercial Banks in Indonesia, with the research sample using the saturated sample method and the data used are NPF, CAR, FDR, and ROA data for Islamic commercial banks for the 2016-2020 period, taken from the official website of the Financial Services Authority, with multiple linear regression analysis as a data analysis technique. Based on the results of the study proves that NPF has a significant negative effect on the profitability of Islamic commercial banks with a regression coefficient of -0.28 and a significant value of 0.00. CAR has no significant effect on the profitability of Islamic commercial banks with a regression coefficient of 0.05 and a significant value of 0.08. FDR has no significant positive effect on the profitability of Islamic commercial banks with a regression coefficient of 0.00 and a significant value of 0.84. With a Prob (F-statistic) value of 0.00, simultaneously NPF, CAR, and FDR have a significant effect on profitability.Keywords: Influence, non performing financing, capital adequacy ratio, financing to deposit ratio, Â profitability